Balanced score card approach for better Shari’ah corporate governance - Htay, Sheila Nu Nu; Syed, Ahmed Salman (Science Publications, 2013)
Islamic financial institutions have emerged due to the non-Shari’ah compliant nature of conventional financial from interest, uncertainty, gambling and prohibited activities from the Islamic perspective. In order to achieve the mission of Shari’ah compliance, organizations such as Accounting and Auditing Organization for Islamic Financial Institutions, Islamic Financial Services Board and countries like Malaysia have provided Shari’ah governance guidelines. However, there are some court-cases regarding non-Shari’ah compliant issues and consequently, this has tarnished the reputation of the Islamic financial institutions. There is no guideline on Shari’ah performance measures available to find out to what extent Islamic financial institutions meet its mission. This study tries to fulfill the needs of the industry by providing the balanced score card for Shari’ah governance. This proposed score card is designed based on the concepts of accountability, responsibility, independence and competency of the Shari’ah board members. It suggests measures how any Islamic financial institutions discharge their fiduciary duty towards shareholders, depositors, participants of Islamic industry. The main drive towards Islamic financial institutions is to provide fair and just financial system free insurance, borrowers and society with the expectation of long-term success of the institutions within the Shari’ah framework. The proposed balanced score card is developed based on the opinions of 7 representatives from Islamic banks and 5 representatives from Takaful (Islamic Insurance) Operators. It is expected that this score card can be used as a platform for improving the Shari’ah corporate governance of Islamic financial institutions.